Multiphoton effects with bright squeezed vacuum - Kopylov, D. A.; Spasibko, K. Yu; Cutipa, P.; Murzina, T. V.; Chekhova, Maria (Optics InfoBase Conference Papers, 2020)
Light generated through strongly pumped parametric down-conversion has extremely strong photon-number fluctuations and is therefore highly efficient for multiphoton effects. In addition, its spectral and spatial properties can be tailored to allow two-dimensional multiphoton spectroscopy.
CRIS-Team Scopus Importer:2020-11-13